2023
DOI: 10.1007/s40828-022-00176-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry in light-induced 3D printing

Abstract: In the last few years, 3D printing has evolved from its original niche applications, such as rapid prototyping and hobbyists, towards many applications in industry, research and everyday life. This involved an evolution in terms of equipment, software and, most of all, in materials. Among the different available 3D printing technologies, the light activated ones need particular attention from a chemical point of view, since those are based on photocurable formulations and in situ rapid solidification via photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 125 publications
(147 reference statements)
0
9
0
Order By: Relevance
“…[ 1b ] This leads to a great opportunity for synthetic organic chemists, as the development of new functional molecules is directly linked to the fabrication of unprecedented functional 3D objects, which could also be the final products with expected applications. [ 2a,3 ] However, two major challenges remain in this area.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1b ] This leads to a great opportunity for synthetic organic chemists, as the development of new functional molecules is directly linked to the fabrication of unprecedented functional 3D objects, which could also be the final products with expected applications. [ 2a,3 ] However, two major challenges remain in this area.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Among the vat-polymerization 3D printing technology, DLP offers the further advantage of higher printing velocity compared to SLA, since a complete layer of material is cured at the same time. 33 To the best of our knowledge, only Yoon et al 34 reported of a device partially fabricated with DLP able to harvest mechanical energy, employing photocurable resins mixed with PTFE powders. In this work, a complex structure was produced to obtain an air filter which also possesses triboelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among all these technologies, vat-photopolymerization (VP) 3D printing, which encompasses SLA and also digital light processing (DLP), are particularly interesting, since those are well-known for being the most flexible techniques to produce functional devices. In fact, in VP is possible to control the functionality both working on the design and on the composition of the printable formulations. , Furthermore, these techniques are characterized by very high resolution as well as the possibility to print multimaterial structures. , Among the vat-polymerization 3D printing technology, DLP offers the further advantage of higher printing velocity compared to SLA, since a complete layer of material is cured at the same time …”
Section: Introductionmentioning
confidence: 99%
“…14–16 Starting from their computer-aided design (CAD) customized fabrication, 3D printing techniques are commonly more cost-efficient and faster than traditional manufacturing technologies. 17,18 These technologies can be divided into two main categories: extrusion-based and lithography-based 3D printers. 19 While extrusion-based technologies are known for their enhanced versatility ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Starting from their computer-aided design (CAD) customized fabrication, 3D printing techniques are commonly more costefficient and faster than traditional manufacturing technologies. 17,18 These technologies can be divided into two main categories: extrusion-based and lithography-based 3D printers. 19 While extrusion-based technologies are known for their enhanced versatility (e.g., fused direct ink writing and fused deposition modeling printers), lithography-based techniques permit the creation of complex and interconnected architectures with the best resolution overall.…”
Section: Introductionmentioning
confidence: 99%